Photodynamic Therapy - Bacci, Stefano; Kang, Kyungsu (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is dedicated to a topic related to the effects of photodynamic therapy organized by Biomedicines in 2022 (https://www.mdpi.com/topics/photodynamic_therapy). In medicine, the use of photodynamic therapy for the treatment of oncological and non-oncological diseases has been widely documented and well codified. In dermatology, the use varies from oncological to the treatment of chronic wounds, as well as in cosmetology for photo-rejuvenation. The 19 manuscripts published in this book cover all aspects of this therapy, including the discovery of new natural and synthetic photosensitizers, biomaterials and nanotechnology, in vitro and in vivo studies, and clinical trials.